2007
DOI: 10.1111/j.1570-7458.2007.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Eat or be eaten: prevalence and impact of egg cannibalism on two‐spot ladybirds, Adalia bipunctata

Abstract: Ladybirds commonly engage in cannibalistic behaviour. Egg cannibalism by first instars is considered advantageous to the cannibal, because it not only results in direct metabolic gain but also a reduction in potential competitors. In this study, we quantified the effect of cannibalism on the development rate and survival of Adalia bipunctata (L.) (Coleoptera: Coccinellidae) larvae through development to the adult stage. We also assessed the synchrony of egg‐hatching in relation to laying order and compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
0
22
1
Order By: Relevance
“…Dispersing fi rst instars risk starvation before fi nding and overcoming their fi rst prey (Banks 1954, Dixon 1959, Kawai 1976, Wratten 1976 ). Initial consumption of sibling eggs may supply critical energy and nutrients, speeding development and increasing survival (Banks 1954, Kawai 1978, Roy et al 2007 ). Osawa (1992c) recorded increasing larval survival to the second instar in Har.…”
Section: Cannibalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Dispersing fi rst instars risk starvation before fi nding and overcoming their fi rst prey (Banks 1954, Dixon 1959, Kawai 1976, Wratten 1976 ). Initial consumption of sibling eggs may supply critical energy and nutrients, speeding development and increasing survival (Banks 1954, Kawai 1978, Roy et al 2007 ). Osawa (1992c) recorded increasing larval survival to the second instar in Har.…”
Section: Cannibalismmentioning
confidence: 99%
“…Another means of adaptive manipulation of sibling egg cannibalism was suggested by Michaud and Grant (2004) , who found that eggs laid singly were less likely to be cannibalized by siblings than were eggs laid near each other. Roy et al (2007) investigated whether hatching much more readily than each other ' s eggs (Agarwala et al 1998 ). Similarly, fourth instar and adult Har.…”
Section: Consumption Of E Ggsmentioning
confidence: 99%
“…Although it can sometimes function to eliminate competitors 1,2 or be the price of mating 3 , it is usually a means of supplementing nutrition [4][5][6][7] . Cannibalism has important ecological consequences for population dynamics and stability, interspecific trophic interactions as well as pathogen transmission and epidemiology [8][9][10] .…”
mentioning
confidence: 99%
“…For predatory animals, cannibalism is a straightforward extension of diet and many predators include conspecifics among their prey 4,11,12 . A broader range of taxa engage in egg cannibalism, facilitated by the small relative size, immobility and defencelessness of eggs 2,6,[13][14][15] , or in predation on much smaller juvenile conspecifics 8,11 . In contrast, herbivores or detritivores are presumably poorly equipped to hunt live conspecifics of size similar to (or larger than) themselves: lacking the morphological and behavioural adaptations of predators, they would be inefficient as hunters and risk injury by the victim defending itself 8,16 .…”
mentioning
confidence: 99%
“…Although the killing of males may seem to be a negative consequence of infection, infected female ladybirds benefit from the death of their brothers by freeing up of resources (resource reallocation), reduced kin competition and avoidance of inbreeding (e.g. Majerus and Hurst 1997;Roy et al 2007). There is therefore an indirect fitness advantage to females from malekiller infection.…”
Section: Bacteriamentioning
confidence: 99%